A Novel Protein Subcellular Localization Method With CNN-XGBoost Model for Alzheimer's Disease - Pang, Long; Wang, Junjie; Zhao, Lingling; Wang, Chunyu; Zhan, Hui (Frontiers in Genetics, 2019)
The disorder distribution of protein in the compartment or organelle leads to many human diseases, including neurodegenerative diseases such as Alzheimer’s disease. The prediction of protein subcellular localization play important roles in the understanding of the mechanism of protein function, pathogenes and disease therapy. This paper proposes a novel subcellular localization method by integrating the Convolutional Neural Network (CNN) and eXtreme Gradient Boosting (XGBoost), where CNN acts as a feature extractor to automatically obtain features from the original sequence information and a XGBoost classifier as a recognizer to identify the protein subcellular localization based on the output of the CNN. Expriments are implemented on three protein datasets. The results prove that the CNN-XGBoost method pferforms better than the general protein subcellular localization methods.